2017
DOI: 10.1016/j.chembiol.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective EphA4 Agonists for the Treatment of ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive degenerative disease that affects motor neurons. Recent studies identified the receptor tyrosine kinase EphA4 as a disease-modifying gene that is critical for the progression of motor neuron degeneration. We report on the design and characterization of a family of EphA4 targeting agents that bind to its ligand binding domain with nanomolar affinity. The molecules exhibit excellent selectivity and display efficacy in a SOD1 mutant mouse model of ALS. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…Motor neuron-specific EphA4 knockdown or the use of an EphA4-blocking recombinant protein administered systemically, had a moderate effect on disease onset in the same model 20,21 . In contrast, the systemic administration of an EphA4-specific agonist improved the survival of SOD1 G93A mice 22 . Therefore, there is a need for additional approaches to better understand the modifying role of EphA4 in ALS.…”
Section: Introductionmentioning
confidence: 86%
“…Motor neuron-specific EphA4 knockdown or the use of an EphA4-blocking recombinant protein administered systemically, had a moderate effect on disease onset in the same model 20,21 . In contrast, the systemic administration of an EphA4-specific agonist improved the survival of SOD1 G93A mice 22 . Therefore, there is a need for additional approaches to better understand the modifying role of EphA4 in ALS.…”
Section: Introductionmentioning
confidence: 86%
“…When receptor and ligand interact, bidirectional signalling occurs downstream of both Ephs and ephrins, giving rise to attractive or repulsive stimuli of two opposing cell membranes [34]. Although the role of EphA4 ligands in ALS is unknown, an EphA4 agonist that impedes EphA4 binding to its ligands, and an EphA4-Fc recombinant protein that reduces binding of EphA4 ligands to the receptor beneficially affected the phenotypes in mouse models for ALS [44, 47].…”
Section: Introductionmentioning
confidence: 99%
“…While beneficial effects were seen in SOD1 G93A mice treated with an EphA4 ectodomain fused to Fc approach for inhibiting EphA4 8 , the complexities of multiple ephrin ligands that are shared between EphA4 and other ephrin receptors as well as of potential differential effects of forward and reverse ephrin-EphA receptor signaling make it hard to confirm a role for EphA4 inhibition in that study. Complexities about how to target EphA4 are also raised by the report that a compound acting as an agonist when tested in in vitro assays prolongs survival in SOD1 G93A mice 7 . Notably that study, which rigorously characterized EphA4 ligands, found no binding of the putative EphA4 inhibitors, compound 1, and rhynchophylline to EphA4 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of a protective role for EphA4 reduction in ALS models, along with evidence suggesting EphA4 inhibition could be protective in mouse models of Alzheimer’s disease, spinal cord injury, and stroke 3 6 , prompted interest in developing EphA4 inhibitors as a potential therapeutic strategy for treating neurodegeneration. Subsequent work designing and characterizing EphA4 targeting agents identified a compound (123C4) that prolonged survival in SOD1 G93A mice 7 . However, that compound was found to act as an EphA4 agonist in cellular assays, raising questions about whether the in vivo benefits were due to EphA4 activation or EphA4 down-regulation following agonist binding.…”
Section: Introductionmentioning
confidence: 99%